Anchoring Pd(OAc)2 on amide-bonded covalent organic frameworks: An efficient heterogeneous Pd@OC-MA catalyst for Suzuki-Miyaura coupling reactions in water. Issue 48 (27th November 2020) - Wu, Shang; Zhang, Ying; Jiang, Hongyan; Wu, Lan; Ding, Ning; Jiang, Pengwei; Zhang, Hong; Zhao, Lianbiao; Yin, Fenping; Yang, Quanlu
Abstract: Nitrogen-rich of a melamine-based mesoporous covalent organic frameworks (COFs) materials were synthesized and used as a carrier to support a Pd(OAc)2 . The Pd@OC-MA revealed an efficient catalytic activity and selectivity for Suzuki-Miyaura coupling reactions in an environmentally friendly water medium at room temperature. Specifically, it had moderate to excellent conversion for inactive chlorinated aromatic hydrocarbons. The catalyst was synthesized simply, had high stability and good selectivity, and was easy to recycle. Excellent catalytic activity of the Pd@OC-MA was also observed after five consecutive cycles. Graphical abstract: Abstract: we have developed Pd@OC-MA: an efficient and stabilized catalyst for Suzuki - Miyaura coupling reactions in an environmental friendly water medium at room temperature. Image 1 Highlights: A stable heterogeneous palladium catalysts, the porous COFs anchored Pd complex, was synthesized by a simple technique. Pd@OC-MA complex is an efficient and stable catalyst for Suzuki-Miyaura coupling reactions in water at room temperature. The catalyst can be separated simply, effectively and reused five times without any activity decrease.